Citizen journalism through Twitter. Case study of Ecuador earthquake of April 16, 2016 - Rivera Rogel, Diana Rivera Rogel (2019)
This article do an approach to the impact of citizen activism during the earthquake of Ecuador on April 16, against the responsiveness of the mass media. The methodology considers the review of the activity of users on Twitter with two tools: Trendinalia and Twitter Reach, during 24 hours following the earthquake. First results indicate the importance of the user activity for informative production; however, Twitter, as an anarchic tool, it was evident the quantity of sources and much of the information was made about emotional issues.